Study on the effects of heterogeneous distribution of methane hydrate on permeability of porous media using low-field NMR technique - Ji, Yunkai; Hou, Jian; Zhao, Ermeng; Lu, Nu; Bai, Yajie; Zhou, Kang; Liu, Yongge (Zenodo, 2019)
Data sets for the Publication 'Study on the effects of heterogeneous distribution of methane hydrate on permeability of porous media using low-field NMR technique' in Water Resources Research.